APLICACIONES ERGONOMICAS de los sistemas de iluminacién en interiores - FLORES BATALLAS, EFRAÍN (2014)
This article deals with the issue of proper lighting design in the labor centers as a basic aspect for the health and welfare of workers. The article focuses on the ergonomic context that must be considered holistically for managers who are concerned with people’s safety. It analyzes different aspects that contribute to good design as in the case of the operation of the visual system, the magnitudes and used units, the chromaticism, the measures to be considered for the proper use of these systems as well as an outline that summarizes the ergonomic analysis. Finally it develops the methodology design of illuminated systems known as "Method of lumens", valid to implant it in indoor premises such as offices, workshops, classrooms and all the facilities that are delimited by walls and roof.